Bologna en la postmodernidad: un laberinto urbano de imagenes sonoras - Tudoras, Laura Eugenia (Revista de Filología Románica, 2009)
The literary configuration of urban space in postmodernity is the result of a combination of multiple languages. The postmodern image of Bologna is a sound image.